Multi-Criteria As Decisions Making Menggunakan Program Linier Dan Integer Programming - Devita, Rischa; Tampubolon, Ferdinan Rinaldo (Universitas Pahlawan Tuanku Tambusai, 2021)
The decision to choose stock assets must be analyzed properly with careful consideration as many series of alternatives so that the results of the selection maximize the achievement of expected profit or benefit. Several alternative decision choices are needed for comparison so that the decision to be taken can achieve its target, namely the right decision to maximize the success. Therefore, a comprehensive approach is needed in choosing a decision so that the results of the decision are in accordance with the success of a profit or benefit. Decision making with several criteria (Multi-criteria as decisions making) is one of the approach methods that can be used to sort out between decisions that are more appropriate or in accordance with existing conditions. Basically, the purpose of this method is so that decision makers can determine the right decision in the situation and conditions experienced with which decision alternative is more appropriate. There are several criteria for an object to be selected and then written in a linear mathematical modeling. The selection of shares to be purchased using the objective function of maximizing returns, and making the Mean Absolute Deviation risk function, a constraint function.